2021
DOI: 10.1021/acsaem.1c03011
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Polymerized Electrolytes with Fully Cross-Linked Networks Boosting High Ionic Conductivity and Capacity Retention for Lithium Ion Batteries

Abstract: In this report, quasi-solid polymer electrolytes (QPEs) based on dicationic imidazolium-based poly(ionic liquid) (PIL) cross-linker end capped with polyethylene glycol (PEG) segments have been UV cured directly onto lithium anode via an in situ solventless strategy, creating a direct, effective, and versatile method for electrolyte production. Depending on the composition, room temperature ionic conductivities are found to vary between 0.7 and 1.1 mS cm −1 , while compressive elastic moduli reveal the values b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The ionic conductivity can reach 1.07 × 10 −3 S cm −1 at room temperature. 277 The lithium-ion transference number (LTN) is one of the important parameters for electrolyte. A high LTN could enable low concentration polarization and suppress the lithium dendrite growth.…”
Section: Organosulfur Additives For Li-co 2 Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…The ionic conductivity can reach 1.07 × 10 −3 S cm −1 at room temperature. 277 The lithium-ion transference number (LTN) is one of the important parameters for electrolyte. A high LTN could enable low concentration polarization and suppress the lithium dendrite growth.…”
Section: Organosulfur Additives For Li-co 2 Batteriesmentioning
confidence: 99%
“…Pentaerythritol tetrakis (3-mercaptopropionate) (PETMP) with a star structure is the most frequently used cross-linker for the highly cross-linked copolymers obtained through the thiol–ene click reactions with ene monomers. Suk et al reported a semi-interpenetrating organosulfur-based solid polymer electrolyte through the reaction of PETMP and the star-shaped hexakis­(allyloxy)­cyclo-triphosphazene (PAL) cross-linker, with poly­(ethylene glycol) dimethyl ether (PEGDME) as a plasticizer . The obtained polymer electrolyte shows a high ionic conductivity of 7.4 × 10 –4 S cm –1 at 30 °C with an electrochemical window of 5.66 V. The Li/LiFePO 4 cell with the electrolyte shows an initial discharge capacity of 147 mAh g –1 at a 0.5 C rate and the capacity retention is 97% after 100 cycles.…”
Section: Organosulfur As Electrolytes In Lithium Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the resulting Li–S bonds are still attached to the conetwork in the form of side branches since the S–S bonds are initially parts of the polysulfide chains before the S–S bond scission by Li cations. Although the Li ions undergoing complexation with the end-capped sulfur of the side branches cannot travel over large distances, these Li ions are still capable of forming polarization, reminiscent of EDLC character, against the electrons at the interface of the NMC cathode containing conductive carbon (Super-P), which was used as part of a PVDF binder to afford electron conduction through a current collector to an outer circuit. Hence, the suggested pseudocapacitor-like character of the CV curves of the PEM in Figure d is plausible. A reverse process can also be anticipated, i.e., S–S can be recombined with continued cycling by releasing Li ions from the Li + –S – bonds since the S–S bond scission by Li ions is known to be reversible.…”
Section: Resultsmentioning
confidence: 99%
“…UV 固化法优势有很多, 比如: 不需要外界提供热 量, 没有能量消耗; 固化时间短; 含有很少量溶剂, 绿 色环保; 固化后的电解质机械强度高 [68] . 如图 9 所示, Tseng 等 [69] 图 9 通过硫醇-烯反应和原位过程形成聚合物固态电解质的示意 图 [69] Figure 9 Schematic diagram of polymer solid electrolyte formation through thiol olefine reaction and in-situ process [69] 5.3 原位聚合法 大多数固态电解质通过溶液浇铸法制备, 在电池外 部成膜后放入电池中. 与液态电解质相比, 非原位制备 的固态电解质存在一些问题.…”
Section: 化 学 学 报unclassified